Governance of resources, processes, outputs and performance measurement of mosques based on Maqasid Al-Syariah / Muhd Fauzi Abd Rahman …[et al.] - Abd Rahman, Muhd Fauzi; Salam, Mursal; Syed Yusuf, Sharifah Norzehan; Mastuki, Nor'azam; Lokman, Norziana; Yaacob, Nathrah; Abdullah, Siti Mariam Melissa (Universiti Teknologi MARA, 2021)
Based on Maqasid Al-Syariah the purpose of this study was to examine the relationship between the four traditional performance measurement variables: resources, processes, outputs, and outcomes to establish a viable performance measurement framework for mosques. The second was to include governance as the fifth variable as part of the performance measurement framework. This study employed a quantitative research method using self-administered questionnaires as the primary form of data collection. A total of 800 questionnaires were distributed, and only 224 questionnaires were received. From that, 210 questionnaires were analysed using Structural Equation Modeling (SEM). Three main findings were obtained. First, the finding found that processes played a significant role in mediating the influence of resources on outputs. Second, the Maqasid Syariah Index had a significant negative association with outputs which indicated that as outputs increase, the objectives of the mosques generally diminish. Therefore, mosques are not able to meet their goals with increased outputs. Third, governance directly affects the resources and outputs of mosques. The governance mechanisms through the application of accountability, disclosure and transparency dimensions directly affected mosque resources. The results of this study provide value to stakeholders of mosques specifically those who are direct recipients of the mosque operations and activities, such as the religious authorities and society.